Differentiation Between the Malignant Mesothelioma of Pleura and Pleural Metastasis with Contrast Enhanced CT, Is It Possible? - Butnian, Krittachat; Muangman, Nisa; Totanarungroj, Kanyarat; Wonglaksanapimon, Suwimon (Siriraj Medical Journal, 2021)
Objective: To compare CT findings between malignant pleural mesothelioma (MPM) and metastatic pleural disease (MPD). Materials and Methods: CT chest images of 157 cases of pathologically-proven malignant pleural disease (21 MPM, 136 MPD) were retrospectively reviewed by two radiologists who were blinded to the diagnosis. Findings of interest included pleural effusion, pleural thickening, organ invasion, lymphadenopathy, dominant lung nodule, pulmonary or extra-thoracic organ metastasis, and asbestos-related disease. Results: Findings commonly found in MPM compared with MPD are circumferential pleural thickening (52.4% vs 14.0%, p<0.001), pleural mass (33.3% vs 7.4%, p<0.001), organs invasion (57.1% vs 9.6%, p<0.001), and asbestos related disease (19% vs 0%, p<0.001). Conclusions: Circumferential pleural thickening, pleural mass, presence of organ invasion, and CT finding of asbestos-related pleural disease were the CT findings that raise the possibility of MPM.